Case Report: Electrophysiological characteristics of the pelvic floor in spinal epidural lipomatosis - Li, Jiaqian; Chen, Bin; Jiang, Hong; Ruan, Weishuyi; Li, Jianhua (Frontiers in Rehabilitation Sciences, 2025)
Electrophysiological examination of the pelvic floor plays a crucial role in localizing nerve damage in pelvic floor dysfunction (PFD). Spinal epidural lipomatosis (SEL) is a space-occupying disease of the spinal canal. SEL can cause spine-related symptoms. We report a case of SEL with pelvic floor dysfunction symptoms and provide two sets of pelvic floor electrophysiological data, before and after disease progression. This case highlights the potential utility of electrophysiological assessment in the early diagnosis and monitoring of SEL.